Wage Determination and Employer Power in the Labour Market for Servants: Evidence from England and Wales, 1780–1834 - Kaiser, Moritz (International review of social history, 2025)
This paper investigates the labour market for female servants in England and Wales between 1780 and 1834, using previously unexplored archival materials alongside qualitative sources. After introducing the dataset, the study provides a micro-level analysis of wage determinants and traces the sources and evolution of employer market power. The findings show that real wages fell substantially during the early decades of the nineteenth century and stagnated throughout the period from 1780 to 1834. Amid rising cost-of-living pressures in the early 1800s, declining real wages were accompanied by increased nominal wage bunching, suggesting greater employer market power. These trends are contextualized with insights from servants’ autobiographies and household manuals. The combined quantitative and qualitative evidence suggests that service labour markets were highly localized, employers coordinated wage-setting and working conditions, and servants faced barriers to job mobility due to living in tied housing, difficulties in recovering unpaid wages, and the critical role of character references. The results indicate that employers in the largest segment of the labour market had considerable wage-setting power, which intensified during the early years of industrialization.